On in-ness: What Cégep teaching keeps teaching me - Olszanowski, Magdalena (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
A first-person essay on the ways that Cégep teaching is different from teaching at a university. The reflection explores how belonging — an "in-ness" — is enacted within a creative arts department by focusing on various experiences from being hired to navigating teaching online during the pandemic. By doing so, the author recognizes how they come to understand and promulgate belonging in the classroom.